Nonsyndromic Bilateral Multiple Impacted Supernumerary Mandibular Third Molars: A Rare and Unusual Case Report - G. Siva Prasad Reddy; G. V. Reddy; I. Venkata Krishna; Shravan Kumar Regonda (Hindawi Limited, 2013)
A supernumerary tooth is that which is present additionally to the normal series and can be found in any region of the dental arch. An impacted tooth is defined as the one which is embedded in the alveolus, so that its eruption is prevented, or the tooth is locked in position by bone or the adjacent teeth. The occurrence of multiple supernumerary teeth in only one patient in the absence of an associated systemic condition or syndrome is considered as a rare phenomenon. The occurrence of supernumerary teeth in the lower molar region is rare. A prevalence of less than 2% of cases occurring in this region has been estimated. Their occurrence presents a clinical problem for orthodontists and oral surgeons. The cause, frequency, complications, and surgical operation of impacted teeth are always interesting subjects for study and research. An impacted tooth can result in caries, pulp disease, periapical and periodontal disease, temporomandibular joint disorder, infection of the fascial space, root resorption of the adjacent tooth, and even oral and maxillofacial tumours. The management of impacted wisdom teeth has changed over the past 20 years from removal of nonsymptomatic third molars to simple observation. The aim of this paper is to present a rare case of bilateral multiple impacted supernumerary mandibular third molars.